ASUHAN KEBIDANAN PADA Ny. D USIA 74 TAHUN DENGAN PROLAPSUS UTERI TINGKAT II DI RUANGAN SANTA ELISABETH DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2018 - Jayanti Tafonao; Aprilita Br Sitepu (Elisabeth Health Jurnal, 2018)
since formerly, In Indonesia, it has been long known the terms prolapsesd uterus and prolapsed upside down. Prolapsed uterus is a very rare condition. The frequency of prolapsed uterus in Indonesia is only 1.5%. Most occur at an older age than a young age. This is caused by weakness of the muscles and fascia structures at a later age. Based on the book of Opname list in Santa Elisabeth room at Santa Elisabeth Hospital Medan period from January 2017 to May 2018 as many as 15 medical records. Based on the list of Opname shows prolapsed uterus at age> 70 years for 5 people and at age> 30-70 years for 9 people and at age <30 years for 1 person.Goals : The writer are expected to be skilled in giving midwifery care to the elderly age of 74 years with prolapsed uterus level II through Varney management approach.Methods: This report was a survey study report with Descriptive method, the location of this case study was at Santa Elisabeth room of Santa Elisabeth Hospital Medan. Subjects of case studies taken by the writer were the Elderly conducted on March 09 to March 14, 2018. Techniques of collecting data were through subjective and objective.data collection.Result: After 5 days of midwifery care for the elderly, by performing vaginal hysterectomy surgery, performing postoperative care well, generally, the condition of mother is good, physical examination results in normal limits, the mother can do the activity as before and the problem is partially resolved .Conclution : Mothers are expected to maintai